Lakes of Turkey: Comprehensive Review of Lake Çıldır - Sidar Yaygır; Abuzer Çelekli; Özgür Eren Zariç (Aquatic Sciences and Engineering)
Lake Çıldır, situated in eastern Turkey, is one of the most noteworthy freshwater lakes in the region, distinguished for its aesthetic allure and its paramount ecological and socio-economic roles. This review thoroughly examines Lake Çıldır, beginning with an introduction that contextualizes its importance. The climatic conditions influencing the lake's dynamics, its hydrographic characteristics, and the physicochemical variables determining its water quality have been specified. Our review synthesizes findings about the lake's biological attributes, including its varied flora and fauna. Detailed sections are dedicated to the fish species, macrophytes, benthic macroinvertebrates, and phytoplankton that inhabit the lake. Using land cover data, temporal changes in the lake's environmental structure have been evaluated. The lake's trophic state and overall ecological health are critically discussed, shedding light on its current status. Furthermore, the potential and existing ecotourism practices around Lake Çıldır are explored, emphasizing its value as a tourist destination. In conclusion, the challenges faced by the lake are addressed, advocating for robust conservation and management initiatives. This comprehensive review of Lake Çıldır's complex ecosystem is a foundation for forthcoming research.